Analysis of Development in the Creative Industry with the Existence of the Craft Sector in Pearl Jewelry in the City of Mataram - Yuridhista, R.; Ariska , Dwi; Xin, Derr; Martin, Weng (Journal Markcount Finance, 2023)
In this case the objective of the research is to be able to find out if there is a separate alternative in the strategy that is owned by the existing development of the creative industry which will be carried out at the pearl jewelery company PT Karyanian which is located at the Matatan location. In this study, the quantitative descriptive method will be used so that later the results of the data can be clearly seen and read, in addition, this description is also used as an explanatory sentence for each result, where the data that will be collected uses the literature review method, so that the data is dsta. The data will be sourced from journals, literature, social media sources and also use data analysis as a data validity. The results of the analysis show that in the strategic industry for creative ideas in the city of Matara itself, there are internal and external factors as measured by SWOT analysis so that these factors have a positive effect.